The effects of vitamin D on chronic wounds - Priyanto, Mufqi Handaru; Miranda, Eliza; Yusharyahya, Shannaz Nadia; Legiawati, Lili; Novianto, Endi; Bramono, Kusmarinah; Krisanti, Roro Inge Ade (Journal of General - Procedural Dermatology and Venereology Indonesia, 2024)
Background: Wounds that fail to proceed through the normal healing process are referred to as chronic wounds, also known as ulcers. Chronic wounds have immeasurable biological, psychological, social, and economic effects, bringing tremendous challenges for patients, doctors, healthcare providers, and healthcare systems. Discussion: This condition is associated with a variety of comorbidities and complex etiologies. The global incidence of chronic wounds is expected to increase with longer life expectancy. Thus, a holistic approach is necessary, such as proper wound management, proper control of comorbidities, and provision of adequate nutrition, including vitamin D supplementation. Vitamin D is an essential pro-hormone for cell differentiation, proliferation, and growth. It affects the skin’s immune response, and is therefore thought to promote wound healing and tissue repair. Many studies have been published on the association between low vitamin D levels and chronic wounds. However, whether or not vitamin D supplementation directly contributes to wound healing still needs to be elucidated. Conclusion: Despite the many reports on vitamin D as an adjuvant treatment for chronic wounds, further large-scale clinical studies are needed to cement the role of vitamin D as an effective standard therapy for chronic wound healing.